Avaliação da associação molecular de complexos metálicos com ligante triazenido 1-óxido - Iglesias, Bernardo Almeida (2008)
In this dissertation were synthetized six compounds, of the which one is free ligand 1- phenyl-3-(4-nitrophenyl) triazene 1-oxide (1) and five are triazenido complexes of [Ni(O2NC6H4NNN(O)C6H5)2(C5H5N)2] (2), [Zn(O2NC6H4NNN(O)C6H5)2(C5H5N)2] (3), [Ag(O2NC6H4NNN(O)C6H4)(PPh3)2] (4), [V(O)2(O2NC6H4NNN(O)C6H4)(C5H5N)] (5) e [Pb(O2NC6H4NNN(O)C6H5)2] (6). The compound (1) were characterized by melting point, infrared and UV/Vis spectroscopy, X-ray diffraction in a single crystal and NMR 1H. The compounds (2), (3), (4), (5) and (6) were characterized by melting point, infrared and UV/VIS spectroscopy, X-ray diffraction in single crystals. The compounds (1) and (2) crystallizes in the triclinic crystal system, space group P(-1), where the triazene 1-oxide ligand (1) presents bifurcated hydrogen bonds formed by dimerics units, and the compound (2) forms the complex octahedric geometry, forming supramolecular intermolecular arrangement through non-classical interactions. The compounds (3) and (6) crystallizes in the monoclinic crystal system, space group P21/n, where the compound (3) shown distortion octahedrical geometry, influenced by intramolecular non-classical interactions, and the compound (6) presents supramolecular intermolecular non-covalent metal-η 6 arene-π interactions. The compounds (4) and (5) crystallized in the monoclinic crystal system, space group P21/c, where the compound (4) is constitute by bulky ligands PPh3, preventing the formation of the interactions, and the compound (5) form supramolecular intermolecular unidimensional arrangement through dimerics units and bridges [VO2]+.